Fines, valores y principios comunes a la propiedad intelectual, al derecho a la competencia y a otros derechos - Juan Carlos Riofrío Martínez-Villalba (Ius Humani. Jornal do direito, 2012)
This paper aims the definition of which are the pourposes, values and common principles of intellectual property, competence law of advertising, consumer and information. It shows how the principles are anchored in values, and these in turn into rights purposes, making palpable the hierarchy such purposes, values ​​and principles have in the legal system. Thus, the outcome of the research is threefold: (i) definition of the purposes, values ​​and principles common to these areas of law, (ii) its interface, and (iii) their ranking.